2019
DOI: 10.24320/redie.2019.21.e24.1973
|View full text |Cite
|
Sign up to set email alerts
|

Asistencia y deserción escolar de la juventud indígena en Secundaria

Abstract: Se presenta evidencia sobre factores que inciden en deserción y asistencia escolar de estudiantes indígenas de secundaria. Primero, diseñamos un modelo para estimar factores que inciden en la brecha de deserción usando la Encuesta Nacional de Ingresos y Gastos de Hogares. Encontramos que uno de los elementos que más incide en deserción escolar de estudiantes indígenas es la lengua. Posteriormente, realizamos investigación cualitativa en secundarias de Yucatán y Chiapas. Los hallazgos apuntan a que los estudian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
0
0
0
2
Order By: Relevance
“…A study on school dropouts carried out by Peguero [89] concluded that students belonging to ethnic groups that suffer from school violence have a higher risk of abandoning their studies. In this sense, indigenous students with strong cultural roots have a higher risk of dropping out of school, since their language is not used in schools, which results in a negative impact on their academic performance [90]. In the field of health, the evidence shows that people belonging to an ethnic group who perceive discrimination against them have an increased risk of suffering from physical and mental pathologies, although it is important to note that the positive correlation between discrimination and illness is stronger in subjects facing discrimination due to gender, age and sexuality [91].…”
Section: Discussionmentioning
confidence: 99%
“…A study on school dropouts carried out by Peguero [89] concluded that students belonging to ethnic groups that suffer from school violence have a higher risk of abandoning their studies. In this sense, indigenous students with strong cultural roots have a higher risk of dropping out of school, since their language is not used in schools, which results in a negative impact on their academic performance [90]. In the field of health, the evidence shows that people belonging to an ethnic group who perceive discrimination against them have an increased risk of suffering from physical and mental pathologies, although it is important to note that the positive correlation between discrimination and illness is stronger in subjects facing discrimination due to gender, age and sexuality [91].…”
Section: Discussionmentioning
confidence: 99%
“…La educación bilingüe intercultural y la formación de personal docente como la prestación general del servicio educativo centra la atención de todos por sus fallas y pobrezas que caracterizan a toda la educación rural y urbana-marginal de México, para de este modo evitar la deserción y abandono escolar temprano (Arcos, 2012;de la Cruz y Heredia, 2019;Van Dijk, 2012). En este punto es donde destaca la labor de esas otras instituciones y organizaciones no oficiales que intentan trabajar para eliminar esas limitantes, y que a través de sus programas de desarrollo regional y de la comunidad suponen un reto para los propios pueblos indígenas, su cultura y su lengua.…”
Section: Conclusionesunclassified
“…Dado que el modelo intercultural está orientado a la conservación de dichos saberes, la lengua indígena transita cotidianamente entre los estudiantes; este papel de considerar la lengua indígena como vehículo de transmisión de conocimientos con el tiempo ha ido desapareciendo y desde el aula no se considera su uso. Esta situación, sin duda, se ha vuelto también un factor que afecta al desempeño de los estudiantes, ya que al no considerar sus saberes previos y la manera de concebir la educación desde el hogar, no le encuentran sentido a la escuela y finalmente optan por abandonar la escuela (Cruz & Heredia, 2019).…”
Section: Introductionunclassified